Ionic-liquid-based approaches to improve biopharmaceuticals downstream processing and formulation - Almeida, Catarina; Pedro, Augusto Q.; Tavares, Ana P. M.; Neves, Márcia C.; Freire, Mara G. (Frontiers in Bioengineering and Biotechnology, 2023)
The emergence of biopharmaceuticals, including proteins, nucleic acids, peptides, and vaccines, revolutionized the medical field, contributing to significant advances in the prophylaxis and treatment of chronic and life-threatening diseases. However, biopharmaceuticals manufacturing involves a set of complex upstream and downstream processes, which considerably impact their cost. In particular, despite the efforts made in the last decades to improve the existing technologies, downstream processing still accounts for more than 80% of the total biopharmaceutical production cost. On the other hand, the formulation of biological products must ensure they maintain their therapeutic performance and long-term stability, while preserving their physical and chemical structure. Ionic-liquid (IL)-based approaches arose as a promise alternative, showing the potential to be used in downstream processing to provide increased purity and recovery yield, as well as excipients for the development of stable biopharmaceutical formulations. This manuscript reviews the most important progress achieved in both fields. The work developed is critically discussed and complemented with a SWOT analysis.